PENGARUH TABUNGAN DAN DEPOSITO YANG DIMODERASI OLEH MOBILE BANKING TERHADAP PROFITABILITASBANK UMUM KONVENSIONAL - Rahmah Rahmah; Rusma Nailiah (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to examine the effect of savings and deposits, moderated by mobile banking, on the profitability of conventional commercial banks. The population in this research consists of conventional commercial banks listed on the Indonesia Stock Exchange during the 2022–2024 period. The data analysis method used is panel data regression, with the data obtained from secondary sources in the form of monthly and quarterly financial reports of conventional commercial banks listed on the Indonesia Stock Exchange for the 2022–2024 period. The results of the study indicate that both independent variables, savings and time deposits, influence profitability. Meanwhile, mobile banking as a moderating variable is able to moderate the relationship between savings and profitability. On the other hand, mobile banking is not able to moderate the effect of time deposits on banking profitability.